Techniques for wildlife investigations : design and analysis of capture data - Skalski, J. R. (Academic Press, 1992)
Techniques for Wildlife Investigations emphasizes the design of field studies and the statistical inferences that can be made from observed changes in animal abundance and populations. The information presented here is of value not only for wildlife management but also for social and economic decision-making related to the environmental effects of human activities on wildlife populations. Biologists, ecologists, biometricians, fish and game managers will find this book invaluable in their work. Key Features * Provides quantitative criteria for designing effective field experiments * Offers statistical methods for analyzing mark--recapture data * Gives examples and recommendations for implementing field studies.